E-Commerce Training for Young Entrepreneurs in Blang Pulo Village - Jullimursyida; Mawardati; Meutia Rahma; Cut Hilma; M. Akbar Husein Srg (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
In this era called the information age, electronic media has become one of the mainstays for communication and business, e-commerce is an extension of commerce by exploiting electronic media, even though the use of electronic media is not yet understood, but business pressure causes business people to want to or not. want to have to use this electronic media. Sales online or e-commerce have many advantages over manual sales, and it also makes it easier for MSMEs (minimum small businesses) to check data from the sales results. Seeing the development of a sophisticated era and increasingly practical human life, it is important for entrepreneurs to install an online sales website to improve the quality of technology-based sales, fast and be able to compete and survive in the business world.The purpose of implementing this socialization activity is to introduce basic knowledge about e-commerce, web design and online promotion. The group that is targeted at this Environmental Village Service is young people who are entrepreneurs in Blang Pulo Village. The methods used are presentations, discussions and simulations. This activity produces a how-to guide and what to do when an entrepreneur wants to increase his sales. With the training and workshops held, the participants gain insight and knowledge about web design and online sales and promotions..